2020
DOI: 10.1002/dmrr.3289
|View full text |Cite
|
Sign up to set email alerts
|

HDL cholesterol is an independent predictor of β‐cell function decline and incident type 2 diabetes: A longitudinal study

Abstract: Background: Experimental evidence indicates that high-density lipoprotein (HDL) may stimulate glucose uptake and improve β-cell function. The aim of this study was to evaluate whether lower levels of HDL may affect the risk to develop type 2 diabetes.Methods: Incident rate of type 2 diabetes and changes in insulin sensitivity and β-cell function over 5.5-year follow-up were examined in 670 non-diabetic subjects stratified in tertiles according to basal HDL levels.Results: As compared to the highest tertile of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 40 publications
0
18
0
Order By: Relevance
“…A recent systematic review and meta-analysis investigated the predictive role of triacylglycerols as a risk factor for cardiovascular disease in people with type 2 diabetes and found that high serum triacylglycerol levels were associated with poor diabetes control and increased risk of cardiovascular disease [75]. Individuals with low levels of HDL-cholesterol have been reported to exhibit a deterioration in beta cell function [76], therefore decreasing triacylglycerol and increasing HDL-cholesterol levels with the use of probiotics, prebiotics or synbiotics may be helpful.…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
“…A recent systematic review and meta-analysis investigated the predictive role of triacylglycerols as a risk factor for cardiovascular disease in people with type 2 diabetes and found that high serum triacylglycerol levels were associated with poor diabetes control and increased risk of cardiovascular disease [75]. Individuals with low levels of HDL-cholesterol have been reported to exhibit a deterioration in beta cell function [76], therefore decreasing triacylglycerol and increasing HDL-cholesterol levels with the use of probiotics, prebiotics or synbiotics may be helpful.…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
“…Collectively, the findings suggest that ApoA-I and HDL have novel and specific roles in the regulation of glucose control. This notion is further supported by a recent clinical study that concludes that individuals with low HDL levels have an increased risk to develop T2D due to a decline in beta cell function over time 17 .…”
Section: Cvd Cardiovascular Diseases CDmentioning
confidence: 72%
“…Another mouse model study determined the link between lower HDL-C and the decreased uptake of glucose by peripheral skeletal muscle owing to a decrease in mitochondrial respiratory function within these cells [ 32 ]. Some prior publications have found that the protective impact of HDL-C in the context of T2DM risk was linked to changes in the function of pancreatic β-cell cells [ 33 ]. Atherogenic dyslipidemia and associated insulin resistance are thought to be driven in large part by increased hepatic free fatty acid flux, [ 27 ] leading to the liver-mediated secretion of particles containing apo-B [ 34 ].…”
Section: Discussionmentioning
confidence: 99%